Path Analysis: Maternal Determinants and Hair Zinc Levels as Predictors of Stunting and Developmental Disorders in Children Under Five - Nunik Ike Yunia Sari; Estin Gita Maringga (Journal of Maternal and Child Health, 2021)
Background:  Stunting that occurs during childhood will have an impact on the condition of cognitive development in the future. The purpose of this study is to determine the risk factors that have a direct and indirect effect on the stunting and developmental disorders in children under five. Subjects and Method: This was a case study located at Gurah Health Center, Kediri, East Java, from August 4th to 29th 2020. A sample size of 100 subjects was selected by randomly. The dependent variables were stunting and developmental disorders. The independent variables were maternal mid-upper arm circumference (MUAC), exclusive breastfeeding, low birth weight (LBW), infants birth length, and hair zinc levels. The data were measured by questionnaire. Hair zinc levels were tested in the laboratory. Quantitative data analysis used path analysis. Results: Child development was directly and positively influenced by the maternal MUAC (b= 0.12; SE= 0.36; p<0.001), birth weight (b= 0.29; SE= 0.15; p= 0.042), birth length (b= 0.37; SE= 0.15; p= 0.011), breastfeeding (b= 0.08; SE= 0.04; p= 0.033), stunting (b= -0.39; SE= 0.10; p <0.001), and hair zinc level (b= 0.58; SE= 0.67; p <0.001). Hair zinc level was positively influenced by birth weight (b= 0.92; SE= 0.04; p <0.001). Child development was indirectly influenced by exclusive breastfeeding, birth length, and zinc levels. Conclusion: Child development is directly and positively influenced by the maternal MUAC, birth weight, birth length, breastfeeding, stunting, and hair zinc level. Hair zinc level is positively influenced by birth weight. Child development ias indirectly influenced by exclusive breastfeeding, birth length, and zinc levels.